(untitled) (Comprehensive Journal of Science, 2025)
This study aims to identify the Murabaha contract for the purchase orderer and to highlight how Murabaha for purchase orders is applied in banks operating in Libya in terms of the procedures followed in its implementation and the extent of compliance with the Sharia controls and standards issued by the jurisprudential councils and bodies regarding the conditions for the validity of this sale. To achieve this goal, The researcher examined the Murabaha procedures, and follow steps were implemented through one of the Islamic windows at Al Wahda Bank, by studying the documentary cycle of this case from the date of submitting the request to purchase the car through Murabaha to the date of receiving the car by the customer benefiting from this service. This research methodology allows the researcher to study the case thoroughly and then generalize the findings to the entire community. The results of this study indicate a lack of adherence to Sharia principles and standards, particularly during the ownership phase at the Al Wahda Bank branch, specifically regarding the actual possession of the vehicle, the separation of guarantors, and the vehicle insurance. The results also indicate shortcomings in the work of the Sharia Supervisory Board. The study recommends developing the skills of its members through training programs that qualify them to apply Sharia-compliant standards and controls specific to Murabaha transactions.